2002
DOI: 10.1161/01.cir.0000043806.51912.9b
|View full text |Cite
|
Sign up to set email alerts
|

Transient Limb Ischemia Induces Remote Ischemic Preconditioning In Vivo

Abstract: Background-Ischemic preconditioning reduces local tissue injury caused by subsequent ischemia-reperfusion (IR), but may also have a salutary effect on IR injury of tissues remote from those undergoing preconditioning. We tested the hypothesis that limb ischemia induces remote preconditioning, reduces endothelial IR injury in humans, and reduces experimental myocardial infarct size. Methods and Results-Endothelial IR injury of the human forearm was induced by 20 minutes of upper limb ischemia (inflation of a bl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

9
518
0
10

Year Published

2005
2005
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 633 publications
(542 citation statements)
references
References 13 publications
9
518
0
10
Order By: Relevance
“…However, the discovery that an IPC stimulus applied to the circumflex coronary artery reduced the size of an MI arising from sustained occlusion of the left anterior descending artery (6) was subsequently extended by the demonstration that the heart could be protected by subjecting a remote organ or tissue, such as kidney, small intestine, liver, or limb, to short episodes of IR, a phenomenon known as remote IPC (7)(8)(9)(10). Application of a tourniquet to the hind limb before prolonged cardiac IR reduced arrhythmias in rats and IS in pigs (9,11). Most recently, a randomized clinical trial was conducted in which patients who received a remote IPC stimulus consisting of three cycles of I 5 and R 5 of the arm before coronary artery bypass graft surgery were found to have significantly reduced postoperative serum levels of cardiac troponin I, which is indicative of cardioprotection (12).…”
mentioning
confidence: 99%
“…However, the discovery that an IPC stimulus applied to the circumflex coronary artery reduced the size of an MI arising from sustained occlusion of the left anterior descending artery (6) was subsequently extended by the demonstration that the heart could be protected by subjecting a remote organ or tissue, such as kidney, small intestine, liver, or limb, to short episodes of IR, a phenomenon known as remote IPC (7)(8)(9)(10). Application of a tourniquet to the hind limb before prolonged cardiac IR reduced arrhythmias in rats and IS in pigs (9,11). Most recently, a randomized clinical trial was conducted in which patients who received a remote IPC stimulus consisting of three cycles of I 5 and R 5 of the arm before coronary artery bypass graft surgery were found to have significantly reduced postoperative serum levels of cardiac troponin I, which is indicative of cardioprotection (12).…”
mentioning
confidence: 99%
“…(6) The discovery that myocardial infarct size could be limited by applying brief episodes of ischaemia and reperfusion to the lower limb (53) resulted in the development of a non-invasive strategy for eliciting RIPC in the clinical arena. (54,55) We and others have demonstrated that brief episodes of ischaemia and reperfusion applied to either the upper limb (non-invasively using a blood pressure cuff) or the lower limb (by invasive clamping of the iliac arteries) is capable of reducing myocardial injury in patients undergoing cardiac surgery (56,57) or surgical repair of an abdominal aortic aneurysm. (58) Interestingly, Ali and colleagues (58) were able to demonstrated renal protection using RIPC of the lower-limb in addition to myocardial protection.…”
Section: Remote Ischaemic Preconditioning: Giving Your Right Arm To Pmentioning
confidence: 99%
“…[96][97][98] Ischemic preconditioning is a phenomenon in which brief periods of nonlethal ischemia, followed by reperfusion, protects local tissue against later episodes of prolonged ischemia and reperfusion. In remote ischemic preconditioning, protection is conveyed to distant tissues or organs.…”
Section: Ischemic Preconditioningmentioning
confidence: 99%
“…More prolonged periods of ischemia (X20 min) and reperfusion cause local endothelial dysfunction and inhibit FMD and the vasodilatory response to acetylcholine. 97,98 In a series of studies, Kharbanda et al 97 and Loukogeorgakis et al 98 showed that a series of three 5-min cuff inflations preserved endothelial function in the contralateral brachial artery when exposed to acetylcholine or more prolonged ischemia (20 min) and reperfusion. In addition, using this remote ischemic preconditioning protocol before coronary artery bypass graft surgery in a randomized, placebo-controlled design, Hausenloy et al 96 showed cardiac protection by lower levels of troponin T postoperatively in the preconditioning group versus the control group.…”
Section: Ischemic Preconditioningmentioning
confidence: 99%